2019
DOI: 10.1111/cyt.12771
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of rapid on‐site cytological evaluation of lung cancer by a trained pulmonologist during bronchoscopy examination

Abstract: Objective Rapid on‐site cytological evaluation (ROSE) in bronchoscopy is a useful ancillary technique. ROSE is usually performed by a cytopathologist or cytotechnologist. However, because of staff shortages and reduced availability, ROSE cannot be performed in every hospital. We aimed to evaluate the accuracy of ROSE when performed by a trained pulmonologist, comparing the diagnosis results with the final diagnosis of cytopathologists. Methods We performed a retrospective cohort study on 125 patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In our study, ROSE was performed by a well trained pulmonologist. Our study showed that the sensitivity and speci city of ROSE in diagnosing malignant lymph nodes were 96.32% and 79.05% respectively, consistent with previous studies of 88.5% and 83.0% (Umeda et al 2019) In previous studies, ROSE was only applied as an ancillary study to evaluate the su ciency of the sampling in EBUS-TNBA (Huang et al 2017) (Gu et al 2017). To better analyze the effects of elastography or ROSE, we combined elastography and ROSE for statistical analysis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, ROSE was performed by a well trained pulmonologist. Our study showed that the sensitivity and speci city of ROSE in diagnosing malignant lymph nodes were 96.32% and 79.05% respectively, consistent with previous studies of 88.5% and 83.0% (Umeda et al 2019) In previous studies, ROSE was only applied as an ancillary study to evaluate the su ciency of the sampling in EBUS-TNBA (Huang et al 2017) (Gu et al 2017). To better analyze the effects of elastography or ROSE, we combined elastography and ROSE for statistical analysis.…”
Section: Discussionsupporting
confidence: 86%
“…ROSE could guide the operator for identifying the sampling site, determining the su ciency of the sample and decreasing the procedure during (Sehgal et al 2020). Meena et al showed that pulmonologists with cytopathology training could perform onsite cytological evaluation of EBUS-TBNA samples, and no signi cant difference in accuracy of the sample was identi ed when compared with cytopathologists (Meena et al 2016;Umeda et al 2019), bene ting the clinical practice. In our study, ROSE was performed by a well trained pulmonologist.…”
Section: Discussionmentioning
confidence: 99%
“…ROSE is a rapid, real-time cytological interpretation technique that accompanies the sampling process. In Europe and the United States, C-ROSE is widely used in diagnostic interventional pulmonology due to its high diagnosis rate for malignant tumors, its ability to diagnose infectious and noninfectious diseases, and its low complications (13)(14)(15)(16). However, there are few studies on the diagnostic value of M-ROSE as a microbiological evaluation technique for determining the pathogenesis of pulmonary infections.…”
Section: Discussionmentioning
confidence: 99%
“…ROSE can also guide the operator in identifying the sampling site, determining the adequacy of the sample, and decreasing procedure duration [ 8 ]. Meena et al showed that pulmonologists with cytopathology training could perform onsite cytological evaluation of EBUS-TBNA samples, and no significant difference in accuracy of the sample was identified when compared with cytopathologists [ 42 , 43 ], benefiting clinical practice. In this study, ROSE was performed by a well-trained pulmonologist; the results demonstrate that the sensitivity and specificity of ROSE in diagnosing malignant lymph nodes were 95.73% and 79.05% respectively, consistent with findings in previous studies of 88.5% and 83.0% [ 43 ]…”
Section: Discussionmentioning
confidence: 99%